Thermodynamic Study of One-step Production from Isobutene to Methyl Methacrylate - Lik Quan Lau; Haiyan Li; Cheng Loong Ngan; Mahashanon Arumugam; Mukhamad Nurhadi; Sin Yuan Lai (Masyarakat Katalis Indonesia - Indonesian Catalyst Society (MKICS), 2022)
Methyl methacrylate (MMA) has emerged as an essential industrial monomer. However, the toxic by-production and shortage supply of MMA in the global market has gained great attention. Herein, a one-step synthesis to produce MMA from isobutene via a direct oxidative esterification process has been demonstrated to curb the aforementioned downsides. Thermodynamic analysis via Gibbs free energy minimization method proved the feasibility of this route via the equilibrium constant. Despite tert-butanol and isobutane showed higher equilibrium constant than isobutene, they should be avoided. Isobutane is highly flammable while the precursor of tert-butanol is exorbitant. Thus, isobutene was selected for the equilibrium compositions screening. Isobutene conversion was 90% and 15% MMA yield at 700 °C and IBN: O2: MeOH ratio with 1:7:1. This route is mainly limited by the generation of side reactions from the reaction of CH3OH and O2. By varying the feedstock ratio at 1:2:1, the MMA yield increased to 25%. Copyright © 2022 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0).